Polymer Electrolytes for Lithium-Sulfur Batteries: Progress and Challenges - Mingxun Jia; Tunan Li; Daotong Yang; Luhua Lu; Limei Duan; Jinghai Liu; Tong Wu (Batteries, 2023)
The lithium-sulfur battery has garnered significant attention from both researchers and industry due to its exceptional energy density and capacity. However, the conventional liquid electrolyte poses safety concerns due to its low boiling point, hence, research on liquid electrolytes has gradually shifted towards solid electrolytes. The polymer electrolyte exhibits significant potential for packaging flexible batteries with high energy density owing to its exceptional flexibility and processability, but it also has inherent disadvantages such as poor ionic conductivity, high crystallinity, and lack of active groups. This article critically examines recent literature to explore two types of polymer electrolytes, namely gel polymer electrolyte and solid polymer electrolyte. It analyzes the impact of polymers on the formation of lithium dendrites, addresses the challenges posed by multiple interfaces, and investigates the underlying causes of capacity decay in polymer solid-state batteries. Clarifying the current progress and summarizing the specific challenges encountered by polymer-based electrolytes will significantly contribute to the development of polymer-based lithium-sulfur battery. Finally, the challenges and prospects of certain polymer solid electrolytes in lithium-sulfur battery are examined, thereby facilitating the commercialization of solid polymer electrolytes.